Clinical Evaluation of Occupational Lead Exposure in Adults of Road Side Market Places of South Kolkata, India - CHATTERJEE, NILENDRA; BOSE, ANIRBANDEEP; DARBAR, SOUMENDRA; ROY, BIKASH; CHATTARAJ, T.K.; PAL, T.K. (Asian Journal of Chemistry, 2010)
Studies conducted throughout the world has established beyond doubt that elevated blood lead levels may lead to detrimental health effects. It is an environmental toxicant that affects nearly every system in the body. Lead is a highly toxic substance, exposure to which can produce a wide range of adverse health effects. There are many ways in which humans are exposed to lead i.e., through deteriorating paint, lead batteries, household dust, bare soil, air, drinking water, food, ceramics, home remedies, hair dyes and other cosmetics. Lead poisoning, the oldest recognized occupational disease, remains a danger for children and adults. In this study blood lead levels of about 232 adults of both sexes, age ranges between 20-40 years, working in road side small markets, food stalls and hotels of South Kolkata were investigated. Very little information on the blood lead distribution of the adults involving these road sides businesses is available. This study was undertaken to determine blood lead levels among adults spend most of their time in day and night besides some most congested main roads and crossings of south Kolkata. The results indicated that blood lead levels in the areas close to main roads ranged from 1.8 to 29.63 μg/dl, with a median level of 12.32 μg/dl. The blood lead levels of 88.94 % of adult equal or exceeded to 10 μg/dl, the current international action levels. Automobile emission, dust, congested traffic, prolonged hours of work in the polluted areas, low nutritional status and lack of education were among the factors associated with elevated blood lead levels.